Answer:
The second and the third one
Step-by-step explanation:
14. (2x - 1)(x + 7) = 0Using the zero factor property, we know that either the first or second terms (or both) must be equal to 0 if their product is 0. We can set each term equal to 0 to find the solutions:
2x - 1 = 0
2x = 1
x = 1/2
x + 7 = 0
x = -7
15. ![x^{2} +3x=10](https://tex.z-dn.net/?f=%20x%5E%7B2%7D%20%2B3x%3D10)
To solve this equation, you first need to set it equal to 0:
![x^{2} +3x=10 \\ x^{2} +3x-10 = 0](https://tex.z-dn.net/?f=x%5E%7B2%7D%20%2B3x%3D10%20%5C%5C%20x%5E%7B2%7D%20%2B3x-10%20%3D%200)
Next, it can be factored:
![x^{2} +3x-10 = 0 \\ (x+5)(x-2)=0](https://tex.z-dn.net/?f=x%5E%7B2%7D%20%2B3x-10%20%3D%200%20%5C%5C%20%28x%2B5%29%28x-2%29%3D0)
Finally, we can solve just like we did above:
x + 5 = 0
x = -5
x - 2 = 0
x = 2
16. ![4x^2=100](https://tex.z-dn.net/?f=4x%5E2%3D100)
First, you can simplify by dividing each side by 4:
![4x^2=100 \\ x^2=25](https://tex.z-dn.net/?f=4x%5E2%3D100%20%5C%5C%20x%5E2%3D25)
Now, set the equation equal to 0:
![x^2=25 \\ x^2-25=0](https://tex.z-dn.net/?f=x%5E2%3D25%20%5C%5C%20x%5E2-25%3D0)
Next, factor:
![x^2-25=0 \\ (x+5)(x-5)=0](https://tex.z-dn.net/?f=x%5E2-25%3D0%20%5C%5C%20%28x%2B5%29%28x-5%29%3D0)
Finally, find the solutions:
x + 5 = 0
x = -5
x - 5 = 0
x = 5
Answer:
![y=\frac{4}{3}x+4](https://tex.z-dn.net/?f=y%3D%5Cfrac%7B4%7D%7B3%7Dx%2B4)
Step-by-step explanation:
Answer:
y=−15
Hope this helps! Please mark Brainliest!